2011
DOI: 10.1016/j.apcata.2010.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Production of hydrogen from dimethyl ether on supported Au catalysts

Abstract: The adsorption and reactions of dimethyl ether (DME) were investigated on Au nanoparticles supported by various oxides and carbon Norit. Infrared spectroscopic and temperature programmed desorption studies revealed that DME adsorbs readily on most oxidic supports. A limited dissociation of DME to methoxy species was established on Au particles by IR spectroscopy. As regards the formation of hydrogen, Au/CeO 2 is the most effective catalyst. On Au/Al 2 O 3 catalyst the main process was the formation of methanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Recently, steam reforming of methanol is receiving attention because of the relative low process temperature (around 300 °C) and simpler reactor configurations [ 32 ]. Nevertheless, due to the high toxicity of methanol, DME is also considered a reliable candidate for hydrogen production by steam reforming (by adopting similar operation conditions of methanol steam reforming and over a bifunctional catalyst, namely an acid function for DME hydrolysis to methanol and a copper-based catalyst for the alcohol reforming), being not toxic and with a high hydrogen content [ 33 , 34 , 35 , 36 ].…”
Section: Dme As Valuable Fuel Of the Futurementioning
confidence: 99%
“…Recently, steam reforming of methanol is receiving attention because of the relative low process temperature (around 300 °C) and simpler reactor configurations [ 32 ]. Nevertheless, due to the high toxicity of methanol, DME is also considered a reliable candidate for hydrogen production by steam reforming (by adopting similar operation conditions of methanol steam reforming and over a bifunctional catalyst, namely an acid function for DME hydrolysis to methanol and a copper-based catalyst for the alcohol reforming), being not toxic and with a high hydrogen content [ 33 , 34 , 35 , 36 ].…”
Section: Dme As Valuable Fuel Of the Futurementioning
confidence: 99%
“…CH 3 OCH 3 + (3-n) H 2 O + n/2 O 2 → (6-n) H 2 + 2 CO 2 (1) The catalytic reforming of DME at moderate temperature consists of two consecutive reactions; first, DME is hydrolyzed to methanol over an acid catalyst, and then methanol is subsequently transformed into a mixture of H 2 and CO x over a metal function with the participation of the water gas shift reaction (WGS). Acidity of the catalyst is supplied by the support, usually γ-Al 2 O 3 , ZrO 2 , WO 3 /ZrO 2 and zeolites such as ZSM-5 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], but also tungstosilicoheteropolyacids, Ga 2 O 3 /TiO 2 and Mo 2 C [24][25][26], whereas the metal function is usually based on Cu (normally CuZn or Cu/CeO 2 ) [27][28][29][30][31][32][33][34][35][36][37][38][39] or Pd (Pd or PdZn) [40][41][42][43], although the use of other metals such as Ni, Pt, Rh, Ru and Au [44][45][46][47][48][49][50]…”
Section: Introductionmentioning
confidence: 99%
“…As the generation of H 2 free of CO is one of the challenges in heterogeneous catalysis, the catalytic behavior of Au has also been tested from this aspect. It was found that supported Au particles effectively catalyze the production of H 2 in the thermal decompositions of HCOOH [6][7][8][9][10], CH 3 OH [11][12][13][14][15][16][17][18], C 2 H 5 OH [19][20][21][22][23] and CH 3 OCH 3 [24] at 423-573 K. Pure, CO-free H 2 was obtained, but only in the catalytic decomposition of HCOOH at higher temperatures [6][7][8]. A further development in this topic was the production of H 2 by photocatalytic decomposition of the above compounds over supported Au samples at room temperature [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%